2019
DOI: 10.1021/acs.jafc.9b00039
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Use of Human Mouth Epidermal Carcinoma (KB) Cells Overexpressing P-Glycoprotein To Characterize Structure Requirements for Flavonoids Transported by the Efflux Transporter

Abstract: This study was aimed to determine the mechanism for flavonoid poor absorption related to P-glycoprotein (P-gp). The cellular uptake (CU) of 40 flavonoids was investigated in P-gp overexpressing KB/multidrug-resistant (MDR) cells. A total of 9 flavonoids, including 5,7,3′,4′-tetramethoxyflavone, with a significant (p < 0.05) CUKBE (2.90 ± 0.146 μmol/g) higher than CUKBP (1.57 ± 0.129 μmol/g) were identified as P-gp substrates. Besides, 8 substrates, including tangeretin, showed a significant (p < 0.05) CUKB (9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…The results indicated that P-gp was overexpressed in KB/MDR1 cells and functioned normally. This finding is consistent with our previous research [26]. Thus, the evaluation results of the cell are effective.…”
Section: Discussionsupporting
confidence: 94%
“…The results indicated that P-gp was overexpressed in KB/MDR1 cells and functioned normally. This finding is consistent with our previous research [26]. Thus, the evaluation results of the cell are effective.…”
Section: Discussionsupporting
confidence: 94%
“…Djiogue et al (2009) reported that genistein containing C5-OH had stronger binding ability to the estrogen receptor than daidzein, which further proved that C5-OH was an active site of flavonoids. Fang et al (2019) found that C3-OH, C5-OH, C3′-OCH 3 , and C4′-OCH 3 had good activity for the binding of flavonoids to P-Glycoprotein. Liu et al (2012) studied the inhibitory effect of polymethoxyflavones (PFM) on Aspergillus Niger in citrus.…”
Section: Discussionmentioning
confidence: 94%
“…We speculated that the C5-OH of ring A is the key site for citrinin reduction. Fischer et al (2012) studied the effects of genistein and daidzein on the immunity of Caenorhabditis elegans. It was concluded that genistein decreased vitellogenin expression, but daidzein increased vitellogenin expression, which showed different trends, which may be related to C5-OH.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking was also performed to investigate the structure-affinity relationship between P-gp and the flavonoids. The results indicated that 3-OH, 5-OH, 39-OCH3, and 49-OCH3 are crucial for the interplay between flavonoids and P-gp (Fang et al, 2019). Epigallocatechin-3-gallate could downregulate the expression level of P-gp and BCRP but could not affect the expression of MDR-associated protein 1 in Adriamycin (ADR)-resistant human leukemia (CEM/ADR) cells (Li et al, 2018).…”
Section: Traditional Chinese Medicine Modulation Of P-gpmentioning
confidence: 97%